Loaded and unloaded jump performance of top-level volleyball players from different age categories - Kitamura, K.; Pereira, L.; Kobal, R.; Abad, C. C. C.; Finotti, R.; Nakamura, F. Y.; Loturco, I. (Biology of Sport, 2017)
The aim of this study was to investigate the differences in loaded and unloaded jump performances between different age categories of top-level volleyball players from the same club. Forty-three volleyball players were divided into four age groups: under-17, under-19, under-21 and professional. Vertical jumping height for squat jump (SJ), countermovement jump (CMJ) and CMJ with arm swing (CMJa) and mean propulsive velocity (MPV) in the loaded jump squat exercise with 40% of the athlete`s body mass were compared among the different age categories, considering body mass as a covariate. SJ and CMJ jump height values were higher for professional and under-21 players than under-17 players (p<0.05). CMJa height was higher for under-21 players than under-19 and under-17 players (p<0.05). MPV in the loaded jump squat was higher for under-21 players than under-17 players (p<0.05). From a general perspective, these results suggest that aging per se is not capable of substantially improving loaded and unloaded vertical jump performances across different age categories of top-level volleyball players. Therefore, to increase the vertical jumping ability of these team sport athletes throughout their long-term development, coaches and strength and conditioning professionals are encouraged to implement consistent neuromuscular training strategies, in accordance with the specific needs and physiological characteristics of each age group.